Converging Paths to Resilience: Analyzing Food and Energy Security Dynamics in SULAMPUA - Basri; Yusri (Hasanuddin Economics and Business Review, 2026)
This study examines the convergence of food and energy security in the Sulawesi, Maluku, and Papua (SULAMPUA) region as a key element of national resilience. Using a dynamic panel model with the Generalized Method of Moments (GMM) on data from 10 provinces (2018–2023), the analysis reveals that food security is strongly supported by agricultural technology assistance, which boosts productivity despite shrinking farmland. Equitable fertilizer subsidies are also critical, while natural disasters require targeted adaptation strategies. On the energy side, declining crude oil production weakens stability, but renewable energy development offers significant potential. However, infrastructure limitations and global oil price fluctuations remain significant challenges. Policy implications underscore the need to integrate food and energy strategies, combining agricultural technology, fertilizer subsidies, and accelerating renewable energy development. Green infrastructure, including clean-energy irrigation systems, can enhance resilience while reducing carbon emissions. Strengthening disaster risk management through early warning systems and local crop diversification is also vital. Additionally, energy price-stabilization policies, such as buffer stocks and fiscal incentives for renewables, are necessary to reduce dependence on global markets. Overall, the findings underscore the importance of a multisectoral, evidence-based approach to building sustainable resilience in the SULAMPUA region.